2021
DOI: 10.1126/scisignal.aaz4382
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB responds to absolute differences in cytokine concentrations

Abstract: The behavior of the NF-κB pathway as a differentiator circuit enables the pathway to track changes in cytokine dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 74 publications
3
45
0
Order By: Relevance
“…This stimulation was specific to TNFɑ; addition of PBS + .1% BSA vehicle to RelA-mScarlet cells yielded no such response (Figure 2B, black trace, top panel). Previous studies have shown that TNFɑ induction leads to a coordinated first wave of translocation into the nucleus, followed by additional damped pulses (8,(30)(31)(32). Individual cell traces showed a similar finding, with some cells undergoing a short, single pulse within the first hour after induction, while other cells displayed two or more pulses of RelA translocation after induction (Figure 2B, inset, top panel).…”
Section: Rela-clasp Is Insensitive To Environmental Inputssupporting
confidence: 70%
“…This stimulation was specific to TNFɑ; addition of PBS + .1% BSA vehicle to RelA-mScarlet cells yielded no such response (Figure 2B, black trace, top panel). Previous studies have shown that TNFɑ induction leads to a coordinated first wave of translocation into the nucleus, followed by additional damped pulses (8,(30)(31)(32). Individual cell traces showed a similar finding, with some cells undergoing a short, single pulse within the first hour after induction, while other cells displayed two or more pulses of RelA translocation after induction (Figure 2B, inset, top panel).…”
Section: Rela-clasp Is Insensitive To Environmental Inputssupporting
confidence: 70%
“…These analyses demonstrate that through post-transcriptional PTP feedback, desensitisation of JAK-STAT signalling renders cells with signal memory by responding to relative fold changes in IFN concentration. In comparison, the NF-κB system can detect absolute increases in cytokine concentration during relatively short (<2h) time intervals (Son et al 2021). Other systems use receptor availability to detect temporal changes in stimulus, for example, relative (fold) changes in early growth response (EGR) protein concentration (Lyashenko et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Underlying mechanisms involve complex regulatory networks with feedback loops that generate outputs depending on the signal type, strength, or duration (Bhalla and Iyengar 1999; Novak and Tyson 2008). For example, the temporal responses of the nuclear factor -κB (NF-κB) transcription factor encode different pathogen-derived molecules and cytokines of the immune system (Adelaja et al 2021; Martin et al 2020; Kellogg et al 2017) and adapts to rapidly changing inflammatory cues (Adamson et al 2016; DeFelice et al 2019; Ashall et al 2009; Tay et al 2010; Son et al 2021). The emergent properties of the cellular signalling networks serve as a paradigm to understand how immune cells process inflammatory cues (Dorrington and Fraser 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a follow-up study ( 66 ) indeed showed that the refractoriness was lost if il-1β was used as a subsequent stimulus instead of TNF-α, demonstrating the stimulus-specificity of this dynamical feature. The importance of the interplay between feedbacks was also been highlighted by a number of studies: a very recent study performed on 3T3 cells on a microfluidics platform shows how IκBs and A20 are key to make NF-κB respond to differences in the concentrations of environmental cytokines and provide a sort of activation memory that, again, was reproduced by mathematical models including both feedbacks ( 67 ).…”
Section: Insights On the Regulation Of Nf-κb Activity: How The Interp...mentioning
confidence: 99%